Efficacy, safety and central nervous system effects after switch from efavirenz/tenofovir/emtricitabine to doravirine/tenofovir/lamivudine. (1st April 2021) - Nelson, Mark; Winston, Alan; Hill, Andrew; Mngqibisa, Rosie; Bassa, Ayesha; Orkin, Chloe; Rassool, Mohammed; Rodgers, Anthony; Teal, Valerie; Kumar, Sushma; Teppler, Hedy
Abstract : Objective: Doravirine is an alternative treatment option for individuals who do not tolerate efavirenz. We assessed efficacy, safety, and CNS effects in adults with HIV-1 and CNS complaints who switched from an efavirenz-based regimen to a doravirine-based regimen. Design: Multicenter, double-blind, randomized trial (NCT02652260). Methods: Virologically suppressed adults receiving efavirenz/emtricitabine/tenofovir (EFV/FTC/TDF), or its components, with ongoing EFV-associated CNS toxicity grade 2 or higher (DAIDS criteria) were switched to doravirine/lamivudine/tenofovir (DOR/3TC/TDF) on day 1 (Immediate Switch Group [ISG]) or after 12 weeks (Deferred Switch Group [DSG]). CNS toxicity data were collected by self-administered questionnaire. The primary endpoint was the proportion of participants with any grade 2 or higher CNS toxicity at week 12. Secondary endpoints included virologic response and effect on fasting lipids. Results: Eighty-six participants (58% men, 56% black, median age 41 years, median 4 years on prior EFV regimen) were enrolled (43 ISG, 43 DSG) and included in the analyses. At week 12, 42% of ISG and 37% of DSG had at least 1 grade 2 or higher CNS toxicity [difference 4.7%, 95% CI (−16 to 25%); P = 0.33]. At 24 weeks postswitch, HIV-1 RNA less than 50 copies/ml was maintained in 95.3% of participants, and fasting lipids were significantly decreased (LDL-cholesterol −11.0, non-HDL-cholesterol −13.2, HDL-cholesterol −7.7, total cholesterol −20.9, and triglycerides −13.0 mg/dl). Conclusion: In participants who had CNS complaints while receiving EFV/FTC/TDF, improvement in CNS toxicities attributable to EFV was not significantly different after switching to DOR/3TC/TDF compared with remaining on EFV/FTC/TDF. Virologic efficacy was maintained and lipid profiles improved after switching to DOR/3TC/TDF. Abstract : Supplemental Digital Content is available in the text